UPAYA GURU MENINGKATKAN MINAT BELAJAR IPAS DENGAN MEDIA WHEEL OF FORTUNE DI SD ISLAM - Rahmad Saleh; Lakoni; Raja Novriadi; Siti Rohimah; Wanda Syafitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine the extent to which the Wheel of Fortune media can improve the learning process of students at Al-Fattah Islamic Elementary School Payo Lebar Singkut. This study uses a qualitative approach, which will be implemented at Al-Fattah Islamic Elementary School Payo Lebar Singkut in the period of September 8 to October 22, 2025. The tools used to collect data are observation, surveys, and documentation. Data analysis techniques used include data collection, consolidation, processing, and extraction. The results of the study indicate that the use of Wheel of Fortune media in the learning process can assist teachers in carrying out their duties. The benefits of using this media can be seen from the increased enthusiasm and motivation of students in participating in the learning process. The increase in students' enthusiasm for learning is reflected in the values ​​​​of the tasks they complete, with indicators including: students become more enthusiastic in learning, more active, feel happier, and do not feel bored in the learning process. Students also pay more attention to teachers and more easily remember the information presented.